Aksesibilitas Penyandang Disabilitas Terhadap Fasilitas Publik - Maspaitella, Semuel Valentino; Piris, Hendry Jhon; Tita, Heillen Martha Yosephine (CAPITAN: Constitutional Law & Administrative Law Review, 2024)
Accessibility is a crucial aspect in ensuring social inclusion and equal rights for people with disabilities. This study examines various public facilities, including transportation, government buildings, health facilities, and other public spaces, in terms of ease of access for people with disabilities. Method: The research used is normative juridical with a statutory and conceptual approach. Results: research shows that although there have been some improvements in providing accessibility, there are still many obstacles faced by people with disabilities. These obstacles include limited disability-friendly infrastructure, lack of easily accessible information, and minimal awareness of the public and policy makers regarding the special needs of people with disabilities. This research suggests the need for increased regulation and supervision, as well as active participation from all relevant parties to create inclusive and accessible public facilities for people with disabilities. In this way, it is hoped that people with disabilities can enjoy their rights fully and participate in social life without discrimination.